Analisis Metode Pembelajaran Pada Anak Penyandang Tunagrahita Di SLB N 5 Kota Bengkulu - Rahayu, Septi; Febrianti, Adel; Soenario, Aulia Putri; Pebriani, Rizia Dwi; Zubaidah, Zubaidah (Faculty of teaching training and education, 2024)
Mental retardation is a term for people who have cognitive and intellectual capacities that are different from people in general or below average. After that, this research shows that the role of teachers is very important in educating children who have special needs such as mentally retarded children, because children with special needs require very extra guidance and direction from parents or teachers. Our focus in this research is 1). How do teachers educate mentally retarded children at SLB Negeri 5 Bengkulu city? 2). How do teachers communicate with mentally retarded children at SLB Negeri 5 Bengkulu City? 3). What obstacles are often encountered when teaching mentally retarded children at SLB Negeri 5 Bengkulu City? The objectives of this research are, 1). To find out how teachers educate mentally retarded children at SLB Negeri 5 Bengkulu City. 2). To find out how teachers communicate with mentally retarded children at SLB Negeri 5 Bengkulu City. 3). To find out what obstacles are often encountered when teaching mentally retarded children at SLB Negeri 5 Bengkulu City. This type of research uses a qualitative approach using data source methods obtained from three types of sources, namely data collection techniques in the form of observation, interviews and documentation.